Two Types of Multilinear Stieltjes Integrals in the Henstock-Kurzweil Sense - Halilović, Armin (Sarajevo Journal of Mathematics, 2024)
In this paper we examine and compare two types of multilinear integrals considering their Stieltjes sums. The convergence of the Stieltjes sums is considered in the Riemann, Moore-Pollard and Henstock-Kurzweil sense. 2000 Mathematics Subject Classification. 28B05, 46G12